Use of Immunoglobulin Y Antibodies: Biosensor-based Diagnostic Systems and Prophylactic and Therapeutic Drug Delivery Systems for Viral Respiratory Diseases - Budama-Kilinc, Yasemin; Kurtur, Ozan Baris; Gok, Bahar; Cakmakci, Nisanur; Kecel-Gunduz, Serda; Unel, Necdet Mehmet; Ozturk, Taylan Kurtulus (Bentham Science Publishers Ltd., 2024)
Abstract:: Respiratory viruses have caused many pandemics from past to present and are among the top global public health problems due to their rate of spread. The recently experienced COVID-19 pandemic has led to an understanding of the importance of rapid diagnostic tests to prevent epidemics and the difficulties of developing new vaccines. On the other hand, the emergence of resistance to existing antiviral drugs during the treatment process poses a major problem for society and global health systems. Therefore, there is a need for new approaches for the diagnosis, prophylaxis, and treatment of existing or new types of respiratory viruses. Immunoglobulin Y antibodies (IgYs) obtained from the yolk of poultry eggs have significant advantages, such as high production volumes, low production costs, and high selectivity, which enable the development of innovative and strategic products. Especially in diagnosing respiratory viruses, antibody-based biosensors in which these antibodies are integrated have the potential to provide superiority in making rapid and accurate diagnosis as a practical diagnostic tool. This review article aims to provide information on using IgY antibodies in diagnostic, prophylactic, and therapeutic applications for respiratory viruses and to provide a perspective for future innovative applications.
Keywords: Drug Delivery Systems; SARS-CoV-2; Humans; Immunoglobulins; COVID-19; Animals; Biosensing Techniques; Antiviral Agents; Respiratory Tract Infections; 3. Good health